Overexpression of adaptor protein Ruk/CIN85 in mouse breast adenocarcinoma 4T1 cells induces an increased migration rate and invasion potential - Horak, I.R.; Drobot, L.B.; Borsig, L.; Knopfova, L.; Smarda, J. (Інститут молекулярної біології і генетики НАН України, 2018)
Aim. To study the effect of adaptor protein Ruk/CIN85 overexpression on the dynamics of migration and Matrigel invasion as well as transendothelial migration of murine 4T1 breast adenocarcinoma cells. Methods. Dynamics of 4T1 cells migration/invasion was monitored in real time using the xCELLigence Real-Time Cell Analyzer (RTCA) DP Instrument equipped with a CIM-plate 16. Transendothelial migration (TEM) of 4T1 cells was performed through the layer of primary mouse lung endothelial cells seeded on gelatin-coated 24-well transwell inserts (8-μm pores).The two-tailed Student’s t-test for unequal variances was used for statistical analysis. Results. Ruk/CIN85-overexpression in 4T1 cells are indices a significantly increased motility, Matrigel invasiveness and migration through endothelial cells layer. Conclusions. The Ruk/CIN85 adaptor protein may play a potential role in the control of metastasis in vivo.